Benefits of Adding Virginiamycin to Arapaima gigas (Schinz, 1822) Diet Cultivated in the Brazilian Amazon. (19th May 2020) - Cavali, Jucilene; Dantas-Filho, Jerônimo V.; Nóbrega, Beatriz A.; Andrade, Lucas Henrique V.; Pontuschka, Rute B.; Gasparotto, Paulo Henrique G.; Francisco, da S. Reginaldo; Junior, Luiz Donizete C.; Porto, Marlos O.
Abstract : The aim of this study was to evaluate the physiological, zootechnical, and environmental benefits of the use of growth-promoting virginiamycin in the pirarucu diet. The research was conducted at the Carlos Eduardo Matiazze Fish Center, Federal University of Rondônia. In this study, 96 pirarucu fish were distributed in excavated nursery, divided into two treatment groups, control (0.0 mg kg −1 ) and treatment (75.0 mg kg −1 ) of feed with virginiamycin, with 8 replications in a completely randomized design. With virginiamycin being incorporated into commercial feed, for 107 days of cultivation, the fish were slaughtered with an average weight of 9.18 kg. Carcass weight, flesh, residues, and internal organs/guts were evaluated to calculate slaughter yields, Spearman's correlation, and subsequently regression. For the quantification of micronuclei, a count of 1, 000 cells per blade was determined. The means of the results obtained were contrasted by the Student's t -test ( α = 0.05). Virginiamycin did not cause oscillations in the limnological variables of the nursery but could reduce micronucleated erythrocytes. The average yields in carcass, flesh, and waste were 67.43, 53.4, and 43.14%, respectively. Virginiamycin provided strong correlations ( ρ 2 ) for better productive yields and lower slaughter residue. The hepatosomatic index indicated a strong relationship between liver weight and fat. Virginiamycin may be recommended for fish farming in pirarucu fattening because it contributes to the productive efficiency and sustainability of the fish farm system.